HIV vaccine candidate activation of hypoxia and the inflammasome in CD14+ monocytes is associated with a decreased risk of SIVmac251 acquisition. (June 2018) - Vaccari, Monica; Fourati, Slim; Gordon, Shari; Brown, Dallas; Bissa, Massimilano; Schifanella, Luca; Silva de Castro, Isabela; Doster, Melvin; Galli, Veronica; Omsland, Maria; Fujikawa, Dai; Gorini, Giacomo; et al.
Abstract Qualitative differences in the innate and adaptive responses elicited by different HIV vaccine candidates have not been thoroughly investigated. We tested the ability of the Aventis Pasteur live recombinant canarypox vector (ALVAC)–SIV, DNA–SIV and Ad26–SIV vaccine prime modalities together with two ALVAC–SIV + gp120 protein boosts to reduce the risk of SIVmac251 acquisition in rhesus macaques. We found that the DNA and ALVAC prime regimens were effective, but the Ad26 prime was not. The activation of hypoxia and the inflammasome in CD14+ CD16− monocytes, gut-homing CCR5-negative CD4+ T helper 2 (TH 2) cells and antibodies to variable region 2 correlated with a decreased risk of SIVmac251 acquisition. By contrast, signal transducer and activator of transcription 3 activation in CD16+ monocytes was associated with an increased risk of virus acquisition. The Ad26 prime regimen induced the accumulation of CX3CR1+ CD163+ macrophages in lymph nodes and of long-lasting CD4+ TH 17 cells in the gut and lungs. Our data indicate that the selective engagement of monocyte subsets following a vaccine prime influences long-term immunity, uncovering an unexpected association of CD14+ innate monocytes with a reduced risk of SIVmac251 acquisition. Distinct monocyte subsets associate with different outcomes of SIV vaccines.